When mycosis fungoides seems not to be within the spectrum of clinical and histopathological differential diagnoses - Monia Di Prete; Andrea Michelerio; Viviana Lora; Carlo Francesco Tomasini; Carlo Cota (PAGEPress Publications, 2024)
The most prevalent primary cutaneous T-cell lymphoma, mycosis fungoides (MF), is characterized by the development of plaques and nodules after an erythematous patchy phase that is non-specific. An infiltrate of atypical small- to medium-sized cerebriform lymphocytes in the superficial dermis, with variable epidermotropism, is the histopathological hallmark of the disease. In more advanced stages of the illness, large-cell transformation may be seen. Early diagnosis of MF can be very challenging based only on histopathologic or clinical findings, so it is critical to have a clinical-pathological correlation. Many atypical variants of MF that deviate from the classic Alibert-Bazin presentation of the disease have been described over the past 30 years, sometimes with different prognostic and therapeutic implications. Clinically or histopathologically, they can mimic a wide range of benign inflammatory skin disorders. To make a conclusive diagnosis in these cases, it is recommended to take multiple biopsies from various lesions and to carefully correlate the clinical and pathological findings. We have outlined the various facets of the illness in this review, positioning MF as a "great imitator", with an emphasis on the more recently identified variations, differential diagnosis, and its benign mimics.